2013
DOI: 10.1093/nar/gkt543
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus 3′UTR regulates viral translation through direct interactions with the host translation machinery

Abstract: The 3′ untranslated region (3′UTR) of hepatitis C virus (HCV) messenger RNA stimulates viral translation by an undetermined mechanism. We identified a high affinity interaction, conserved among different HCV genotypes, between the HCV 3′UTR and the host ribosome. The 3′UTR interacts with 40S ribosomal subunit proteins residing primarily in a localized region on the 40S solvent-accessible surface near the messenger RNA entry and exit sites. This region partially overlaps with the site where the HCV internal rib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
69
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(76 citation statements)
references
References 48 publications
7
69
0
Order By: Relevance
“…1a). These results showed the importance of the 39 UTR in the modulation of viral translation and were similar to those obtained by others (Bai et al, 2013;Bung et al, 2010;Song et al, 2006). The mechanism behind the stimulatory effect of the individual 39 UTR regions on viral translation remains to be determined.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…1a). These results showed the importance of the 39 UTR in the modulation of viral translation and were similar to those obtained by others (Bai et al, 2013;Bung et al, 2010;Song et al, 2006). The mechanism behind the stimulatory effect of the individual 39 UTR regions on viral translation remains to be determined.…”
Section: Resultssupporting
confidence: 90%
“…However, the mechanism of 39 UTR enhancement of translation remains to be clearly defined. Possible mechanisms of this stimulatory effect include RNA-RNA interactions with the HCV IRES, recruitment of cellular factors to the 39 UTR that interact with components of the translational machinery present on the IRES and the recycling of ribosomes (Bai et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…This circularization may be promoted by proteins, in particular by RNA helicases (Ariumi et al 2007;Isken et al 2007;Jangra et al 2010) that might be involved in resolving and forming base-pairing interactions between RNA secondary structures at the genome ends. Furthermore, other studies showed that the 3 ′ UTR stimulates RNA translation (Song et al 2006 and references therein), and a recent study suggested that the 3 ′ UTR is also associated with the ribosomal 40S subunit (Bai et al 2013). Currently, we can only speculate what occurs first, if binding of both genome ends to the ribosome facilitates genome end hybridization, or if hybridization of the 3 ′ X region to those regions of the 5 ′ UTR which are not directly involved in ribosome binding facilitates stimulation of translation by the 3 ′ UTR and paves the way for minus-strand initiation by genome circularization.…”
Section: Resultsmentioning
confidence: 97%
“…Of particular relevance is that the 3Ј-UTR of HCV also binds to the 40S subunit. This is not essential for but greatly enhances activity of the IRES at the 5Ј-end (64). Thus, as in BTE-containing mRNAs, the 5Ј-and 3Ј-UTRs can interact simultaneously with the 40S subunit, similar to the cyclization proposed for capped and poly(A) tail mRNA, where the cap and poly(A) tail act synergistically to promote efficient translation.…”
Section: Discussionmentioning
confidence: 87%